Free market institutions and FDI performance in emerging Asian economies - Klimis Vogiatzoglou (International Journal of Management and Economics, 2016)
This paper examines long-term developments in the quality and efficiency of free market institutional systems across thirteen emerging economies from South, South-east, and East Asia over the 1995-2014 period. The paper also empirically assesses the impact of free market institutions on a country's inward foreign direct investment (FDI) performance. We find that the free market institutional framework in most economies is still relatively inefficient, restrictive, and underdeveloped but has, nevertheless, substantially improved during the last twenty-year period. Our empirical results also indicate that a free market institutional system in a host-country is a factor that attracts inward FDI to emerging Asian economies by multinational companies. Consequently, policy makers should focus on further improving the quality of free market institutions.
Keywords: P14; P48; F21; F23; O53; 650; economic institutions; multinationals; FDI; Asia; developing countries